PENINGKATAN KUALITAS PAKAN AYAM DENGAN PENAMBAHAN ENZIM : Pengaruh enzim terhadap nilai daya cerna, neraca nitrogen dan neraca energi. - Patuan L.P. Siagian (Jurnal Kimia Terapan Indonesia, 1998)
In order to improve the feed quality, enzyme preparatories were added to the diets, wich all of the main components were plant origin. Five treatments in a completely randomized design were 9 fold replicaed, namely: 1. Diet without enzyme addition (control), 2. (-glucanose added to the diet), 3. Hemicellulase added to the diet, 4. Cellulase added to the diet, 5. (-glucanase, hemicellulase and cellulase added to the diet. To ascertain the digestibility of the nutrients of the treated diets, a total of 90 male chicks of LSLBrown were selected and kept in a climate conditioned room (temperature 22 °C, relative humidity 65-70 %, lighting 24 hours per day of 20-25 Lux).The results of this experiment showed that the addition of the enzyme to the diet effected Significantly the digestibility of the fat (p 0,001),ash (p . 0,05) and sugar (p 0,05). The addition of combined (-glucanase, hemicellul ase, and cellulase to the diet improved feed conversion ratio of 9, 7 % compared to the control. The nitrogen effictenoy ratio and anergi efficiency ratio were also significantly better (p O,05), each of 9.8 % and ll.8 %.